MIX CULTURE INOCULANT PRODUCTION OF PHOSPHATE SOLUBILYZING AND INDOLE ACETIC ACID (IAA) PRODUCER RHIZOBACTERIA WITH AMBARAWA PEAT SOIL RAWAPENING AS CARRIER - Raharjo, Budi; Suprihadi, Agung (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT---Plant production development  is the main goals  that do for increase the farming quality to fulfill the man needed  in  food. One of the ways is intensive farming, by using organic or inorganic  fertilizer. Phosphate is the essential  for plants. IAA is the necessary plant regulator for the root. Both phosphate  and IAA need in  plant  growing  and production.  Biological  fertilizer  is  fertilizer  with  microbial  as the main material. Bacillus sp.DUCC-BR-K1.7, Bacillus sp. DUCC-BR-KI3, Bacillus sp.DUCC-BR-KI.2b  and Pseudomonas fluorescens, Azotobacter chroococcum, Azotobqcter vinelandii, Azospirillum sp. and Azotobacter brazilensis are bacteria that can solubilization  the phosphate  and IAA  synthesize.  Those bacteria can be used as  inoculants or biological  fertilizer  that put on carrier. One way to support  the aim is giving  the altemative carrier with  suitable composition. The carrier should be support bacterial life  during the storage.  The aim ofthis  research  is find  ths right  consortia so can be used to optimized  viabilities  of  culture Bacillus  sp. DUCC-BR-KIJ,  Bacillus sp. DUCC-BR-K1.3, Bacillus sp. DUCC-BR-KI.2b, P. flourescens, A. chroococcum, A. vinelandii, Azospirillum  sp., and  A. brazilensis in mix  culture  on peat soil  as carrier. This research done in Microbiology Laboratory of Biology Department Diponegoro University. Subculture and activated culture in Nutrient  Broth medium, make the growth curve to the biomass production, make the inoculums, prepare the peat soil, biomass production and mixed biomass with  the carrier, enumeration bacterial culture viability  test in carrier during the storage  by TPC method.  The  results  show  that  all  consortia  culture  bacteria viabiliry Bacillus  sp. DUCC-BR-KI.3  with Azospirillum (A) and Bacillus  sp. DUCC-BR-K1.7, with P.  flourescens (B)  still viable and increasing number of population during seven weeks storage with  l0 t-n CFU/g at To and up to  l0 r3-ro CFU/g at  the end storage. The  consortium  C  between Bacillus  sp.  DUCC-BR-KI.2  b  and A-  brssilensis  increasing  the  number  of population  and  still viable during eight weeks  storage  (1013  - 1014  CFU/g).Key words: biofertilizer, peat soil, viability,  mix cultare, consortiumPermalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3138